2010
DOI: 10.1007/s00125-010-1987-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in patients admitted to hospital with diabetes mellitus aged 30 years and over: record linkage studies

Abstract: Aims/hypothesis The aim of this study was to determine the risk of cancer in people admitted to hospital for diabetes mellitus when aged 30 or older. Methods This study involved the analysis of two statistical datasets of linked hospital and mortality data, in an area in southern England, between 1963 and 1998 Conclusions/interpretation Diabetes mellitus was associated with an elevated risk of some site-specific cancers and a reduction of risk of others. Considering the risk in diabetes of all cancers combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 33 publications
6
71
0
1
Order By: Relevance
“…It is unlikely that glucose-lowering agents can cause pancreatic cancer within days of starting medication. Decreased rates of prostate cancer and NMSC have been reported in the literature [12,13] and also found in the present study. But the evidence is inconsistent for colorectal and breast cancer.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is unlikely that glucose-lowering agents can cause pancreatic cancer within days of starting medication. Decreased rates of prostate cancer and NMSC have been reported in the literature [12,13] and also found in the present study. But the evidence is inconsistent for colorectal and breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to the association between type of cancer and diabetes, pancreatic cancer is one of the types most strongly associated with diabetes, as found in the present study and reported in literature [12,13]. The most likely explanation for this increased risk of pancreatic cancer is protopathic bias; an alternative explanation is detection bias.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…From these 44 studies, 18 were rejected because they did not focus on incidence of lymphoma, leukemia, or myeloma; did not focus on DM2; or were cross-sectional. Finally, 26 studies (13 prospective cohort 10-22 and 13 case-control [23][24][25][26][27][28][29][30][31][32][33][34][35] ) were included in our analysis. …”
mentioning
confidence: 99%
“…Some prospective studies reported that DM determined by questionnaire or medical records is positively associated with gastric cancer, [3][4][5][6] but others found a null association. [7][8][9][10][11][12] However, DM can be easily misclassified when based on self-report of disease in questionnaire survey or medical records. To overcome this problem, several studies were directly based on diabetic biomarkers, such as hemoglobin A1c (HbA1c) and blood glucose, but the associations were also inconsistent in these prospective studies.…”
mentioning
confidence: 99%